The Firm-Level Impacts of the COVID-19 Pandemic : Round 5 Results - World Bank (World Bank, Washington, DC, 2020)
The economic impact of the second wave of the Coronavirus (COVID-19) pandemic remains significantly more severe on businesses than the first, according to the World Bank’s firm-level survey. As government stay-at-home orders persist, the overall share of temporary closures among firms has slightly increased in October 2020. Different regional mandates have yielded varying degrees of temporary closures across Myanmar with almost half of all firms in Yangon temporarily closed, double the national average. This brief focuses on the survey results that was administered between October 13 and 28, 2020 and covered a nationally representative sample of five hundred firms.